Secondary proteolysis in Serra cheese during ripening and throughout the cheese-making season - Macedo, Angela C. (2011)
Experimental Serra cheeses were manufactured from raw ewe’s milk and thistle flowers following a two-way factorial design. The content of nitrogen soluble in water (WSN), in 2% trichloroacetic acid (2% TCA-N), in 12% TCA (TCA-N) and in 5% phosphotungstic acid (5% PTA-N), and the pH and salt-in-moisture concentration were measured throughout the ripening period (sampling at 0, 7, 21 and 35 days) and the cheese-making season (sampling in November, February and May). Proteolysis in 35-day-old Serra cheese was quantitatively high [average values of 34.6% and 11.9% for WSN/TN (total nitrogen) and 2% TCA-N/TN, respectively], but qualitatively low (average values of 5.8% and 1.2% for 12% TCA-N/TN and 5% PTA-N/TN, respectively). The ratios WSN/TN and 2% TCA-N/TN were lowest for cheeses ripened in February, whereas the ratio 12% TCA-N/TN was highest for cheeses ripened in November. By 35 days of ripening, the average pH and salt-in-moisture concentration values were 5.2 and 4.8%, respectively. No correlation was found to occur between the measured pH or salt-in-moisture concentration and the values of soluble nitrogen fractions throughout the cheese-making season.